Evaluation And Use Of Special Collection Perspective Of KNLS - S Kinya, Henry D (Advances in Social Sciences Research Journal, 2018)
Users in public libraries’ needs are changing, technology is changing, the economic environment is changing, distribution of information channels are changing and so, Public libraries should change their roles and approaches to achieve its goal by availing of special collection and special services to users. In assisting information users to access and use not only online special information services but also access other websites special collection services the role of public libraries within the information age context is changing from that of information provider to that of service provider and so is the roles of librarians; changing its old-age manual operations of print to print service to that of library networking to facilitate information sharing services and activities fundamentally requires the new dimension of trained and available enabling environment of ICT in public library system in Kenya. Users’ opinion, views and feelings account most in the fulfillment of the core objectives the Public library is established for. This paper, discusses the public library special collection in the format of; rare books, manuscripts, photographs, archives, artifact, historical photos, unique materials and pamphlets. Therefore researcher has surveyed them in all 32(100%) public libraries in Kenya. This research paper is further, intended to help public libraries librarians, managers and management to decide how to integrate ICT resources special collection in such a way that most users can understand them well enough to make productive choices to foster research. It compiles usability test data evaluating special collection and services offered in library public libraries in Kenya. This research paper describes the progress and application of a fundamental comparison typical which allows librarians to quantitatively measure library special collection services apparent quality, satisfaction and constancy with a library as well as the degree to which exact elements of a library’s program, collections and setting donate to those perceptions……Library professional protocol and standards are in safe hands of both users and staff who are skillfully trained in technical, analytical and information management and repackaging skills; to further provide library information services like subject specialists and subject analyst equipped with special skills to deal with children information needs and users with special needs. In this paper special collection and special services offered to special users in Kenya National Library Services (KNLS) via public libraries in Kenya has been discussed.